2020
DOI: 10.3168/jds.2019-17078
|View full text |Cite
|
Sign up to set email alerts
|

Herb species inclusion in grazing swards for dairy cows—A systematic review and meta-analysis

Abstract: A systematic review and meta-analysis were conducted to estimate the effect of herb species on milk production and urinary nitrogen (UN) excretion from grazing dairy cows. Grazing swards consisting of herb species grown with either a grass species or a grass and legume (multispecies swards) were compared with non-herbcontaining swards consisting of a grass species grown as a monoculture or grass-legume swards (simple swards). A literature search was completed using the online databases CAB Direct, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…More recently, there has been growing research and agricultural industry interest in multispecies swards, and the potential that these offer for simultaneous delivery of environmental gains along with improved livestock performance ( Huyghe et al, 2012 , Grace et al, 2019 , McCarthy et al, 2020 , Cummins et al, 2021 ). More complex grasslands, such as these and semi-natural grasslands, allow greater opportunities for selective feeding, and the choices made by grazing animals can have a marked effect on floristic diversity.…”
Section: What Is Being Grazed?mentioning
confidence: 99%
“…More recently, there has been growing research and agricultural industry interest in multispecies swards, and the potential that these offer for simultaneous delivery of environmental gains along with improved livestock performance ( Huyghe et al, 2012 , Grace et al, 2019 , McCarthy et al, 2020 , Cummins et al, 2021 ). More complex grasslands, such as these and semi-natural grasslands, allow greater opportunities for selective feeding, and the choices made by grazing animals can have a marked effect on floristic diversity.…”
Section: What Is Being Grazed?mentioning
confidence: 99%
“…This increased understanding of pasture nutritive value, in regard to rumen turnover, metabolisable energy (ME) supply and post-ruminal AA flows, can aid in the development of future nutritional strategies to increase the efficiency and productivity of pasture-based systems. Such nutritional strategies could include development of improved pasture management practices (O'Donovan et al, 2002), optimisation of concentrate supplementation (Baudracco et al, 2010), selection of superior plant genetics (Lee et al, 2012) and the development of binary or multi-species pastures (McCarthy et al, 2020).…”
Section: Developments In Nutrition Of Dairy Cowsmentioning
confidence: 99%
“…Diverse swards which incorporate a variety of legume and forb species may, therefore, increase herbage production, benefitting livestock performance, and may also improve soil nutrient retention and reducing leaching. Multispecies swards have been demonstrated to have dry matter yields comparable to grass-only or grass plus clover swards (Vibart et al 2016;McCarthy et al 2020). For instance, Vibart et al (2016) reported mean annual dry matter yields of 11,101 kg ha −1 and 12,021 kg ha −1 for simple and diverse pastures respectively.…”
Section: Agronomic Benefits Of Diverse Swardsmentioning
confidence: 99%